Toil, Soil, and Spoils: The Unemployment Relief Scheme for Archaeological Purposes, from 1934 to 1940 - Barrett, Rachel (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
In 1934 a programme of relief schemes was devised by the Irish government to address chronic unemployment throughout the country. The inclusion of archaeological excavations was a significant step forward for the under-funded Irish archaeological sector as a whole as it committed the government to a programme of systematic excavations over a defined period for the very first time. Between 1934-40, forty State-sponsored research excavations were carried out under the Unemployment Relief Scheme. The identification of an archive collection detailing the administration of thirty-three of these excavations has dictated the focus of this research. This thesis documents this key opportunity that saw the Irish archaeology sector transform professionally and examines how this ambitious programme was coordinated by Harold Leask (Board of Works) and Adolf Mahr (National Museum of Ireland). The primary objective of the U.R.S. excavations remained the pursuit of knowledge, to establish a better understanding and more accurate chronology of archaeological features. Key factors used to select sites to the excavation programme are identified, as well as reasons for rejecting potential sites. Through an examination of working conditions, the unemployed workers are given a voice for the first time. Their contribution allowed the professional archaeologists to focus on the more technical requirements of excavation. The wider archaeological community willingly offered their services to the U.R.S. as supervisors. These excavations also became a training ground for young Irish archaeologists, many of whom acquired sufficient skills to later supervise their own excavations. The progress and results of the investigations were shared through a range of media, making significant contributions to both the national and international archaeological record. This research provides a comprehensive examination of this programme of excavations, to determine its specific contribution to the advancement of the Irish archaeological sector in the 1930s.
APPROVED